A CASE STUDY OF EFFECTIVE EMPLOYEES GRIEVANCE REDRESSAL AT NATIONALIZED BANK OF INDIA (International Journal of Psychosocial Rehabilitation, 2020)
Employees differ as individuals in their needs, expectations, and behavior. When their needs are not satisfied or their objectives are not achieved, the result is employee dissatisfaction. The grievance redressal procedure of an organization enables employees to air their dissatisfaction. It is important for an organization to have an effective grievance redressal system. The HR manager should immediately identify all grievances and must take appropriate steps to eliminate the causes of such grievances so that the employees remain loyal and committed to their work. Effective grievance management is an essential part of personnel management. This research is conducted to study the effectiveness of the grievance redressal procedure of one of the nationalized banks of India. This paper includes various factors that are taken into consideration for measuring the job satisfaction among the employees. This research also takes into consideration the methods adopted by the organization for handling and resolving the conflict. The paper reveals that the grievance handling procedure is satisfactory. The organization is recognizing the importance of satisfying the employees and retaining them. Further improvements can be made so that all members are highly satisfied with the procedure. The suggestions and recommendations, when implemented, will still more benefit the organization. Most of the surveyed employees are satisfied with the method adopted by the organization for redressing the grievances or complaints of the employees.